Secagem de sementes de Arachis hipogae L. com capa protetora - Nascimento, Bruna de Souza (2009)
Arachis hipogae L. peanut is an orthodox seed that must go through a drying process to become free from aflatoxin. The fruit is formed by a system made up by a nucleus and a resistant involucre that constitutes a heterogeneous mixture. So as to contribute to the improvement of those seeds drying, the objective of this study is to analyze the drying of the compound system and its subsystems in relation to moisture transport and shrinkage, as well as the influence on physiological and physical characteristics. In order to do so, the fruit, the seeds with and without endocarp, as well as the pericarp were placed in a forced convection dryer. To approach the problem, the idea of fluid flow on submerged bodies was adopted. The experiments were conducted based on a 32 experimental planning with temperatures of 30, 40 e 50°C and velocities of 0,5; 1,0 e 1,5 m/s. The intermittent method was used to measure the samples mass and to obtain the images. Analysis of the physical and physiological characteristics was performed from observations during the experiments. The results showed that the diffusive transport of moisture was predominant when the fruit and seed with and without the endocarp are concerned. The convective mechanism was also observed for the pericarp. As far as the physical barriers effect is concerned, it was verified that the pericarp and the endocarp cause resistance to mass transport. It was possible to verify the development of the seed s (with and without the endocarp) superficial concavity through image analyses with the aid of IMAGE PRO PLUS® software. However this deformation was not observed for the fruit or for the pericarp. The dimension reductions demonstrate the presence of the shrinkage phenomenon for the seed with and without the endocarp. The results regarding the physiological and physical characteristics showed dependency on operational conditions used when the seeds are processed outside the pericarp. Analysis concerning the process interaction with the product characteristics demonstrated that convective drying is a promising technique having a better relation between the process and quality for the product. Due to the results obtained, the discrimination of the equations that represent drying kinetics with focus on the improvement of seeds production was performed. The advancements obtained contribute to the drying studies of seeds that present protective cover under the perspective of seeds drying engineering.